EXPLORING THE POTENTIAL ROLE OF OMEGA-3 FATTY ACIDS IN DEPRESSION - Natalia Pawelec; Weronika Mazur; Edyta Hańczyk; Dawid Piecuch; Szymon Kopciał; Karolina Kornatowska; Anna Drużdżel (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Depression represents a major public health challenge, affecting individuals worldwide and remaining a prevalent condition that significantly reduces quality of life. Despite the availability of various therapeutic options, including pharmacological interventions, these treatments are often insufficiently effective. Consequently, the search for safe and effective strategies to alleviate depressive symptoms remains a priority. Numerous studies have examined the potential role of omega-3 fatty acids in both the prevention and treatment of depression. In this context, the involvement of inflammatory processes and stress-related pathophysiological mechanisms appears to be particularly relevant. Therefore, research continues to investigate the potential relationship between omega-3 fatty acid supplementation and clinical improvement in patients with depression.Aim of Study: The purpose of this review is to explore potential novel therapeutic strategies that may benefit patients with depression.Material and methods: This narrative review synthesizes contemporary evidence regarding the role of omega-3 fatty acids in the prevention and treatment of depressive disorders. A targeted literature search was conducted using PubMed and Google Scholar. The search was focused primarily on studies published within the five-ten years. Search terms included combinations of “omega-3 fatty acids,” “eicosapentaenoic acid,” “docosahexaenoic acid,” “major depressive disorder,” “treatment-resistant depression". Randomized controlled trials, clinical trials, meta-analyses, systematic reviews, and high-quality narrative reviews were prioritized. Consistent with the narrative nature of this review, no formal systematic screening protocol, risk-of-bias assessment, or quantitative synthesis was performed.Results and Conclusions: After examining the effects of omega-3 fatty acids in patients across different age groups, both as monotherapy and in combination with other agents, including postpartum women, studies have not produced conclusive evidence directly supporting their beneficial impact on depression.